2021
DOI: 10.1136/ijgc-2020-002072
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum breast cancer: mechanisms underlying its worse prognosis, treatment implications, and fertility preservation

Abstract: Breast cancers that occur in young women up to 5 to 10 years' postpartum are associated with an increased risk for metastasis and death compared with breast cancers diagnosed in young, premenopausal women during or outside pregnancy. Given the trend to delay childbearing, this frequency is expected to increase. The (immuno)biology of postpartum breast cancer is poorly understood and, hence, it is unknown why postpartum breast cancer has an enhanced risk for metastasis or how it should be effectively targeted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…However, even after adjusting for age at diagnosis, prognosis was significantly poor (20) [20]. Several previous studies of young breast cancer patients have shown that breast cancer within 5-10 years of delivery has a worse prognosis than that of breast cancer in nulliparous women (46)(47)(48). Many preclinical studies have suggested that it this related to a developmental tissue remodeling process of mammary gland involution (9-11, 13, 23, 49), which may result in distinct gene expression profiles.…”
Section: Discussionmentioning
confidence: 94%
“…However, even after adjusting for age at diagnosis, prognosis was significantly poor (20) [20]. Several previous studies of young breast cancer patients have shown that breast cancer within 5-10 years of delivery has a worse prognosis than that of breast cancer in nulliparous women (46)(47)(48). Many preclinical studies have suggested that it this related to a developmental tissue remodeling process of mammary gland involution (9-11, 13, 23, 49), which may result in distinct gene expression profiles.…”
Section: Discussionmentioning
confidence: 94%
“…6 Therefore, age at diagnosis, parity status and breastfeeding history are important risk factors for breast cancer. 7,8 PPBC is associated with worse survival rates presenting two-to threefold increased risk of death in both ER+ and ER-disease. 6,9,10 Interestingly, studies have shown that diagnosis during pregnancy is not associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In both murine and human mammary glands, postpartum involution begins with controlled apoptosis of mammary epithelial cells. 7 In this process, a minority of mammary epithelial cells survives the death and resistance to cell deaths can probably play an important role in tumor initiation, as it results in the propagation of potentially harmful mutations that allow unregulated growth and division. 13 In this case, the patient PPBC was diagnosed as metaplastic breast carcinoma (MBC) of high histological grade which is a subtype of triple-negative breast cancer and accounts for approximately 1% of all breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends 150 min of moderate-intensity physical activity per week for pregnant and postpartum women to help further heal and improve women's mental health (Bull et al 2020 ; Neil-Sztramko et al 2014 ). Recent studies have also identified potential targets for treating PPBC, including pathways related to lymphangiogenesis and immunomodulation, offering hope for treating these patients (Lefrère et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%